PELAKSANAAN PUTUSAN PENGADILAN TERHADAP HAK ATAS TANAH KREDIT KOPERASI PRIMER ANGGOTA (KKPA) KUD LANGGENG DESA HULU TESO KECAMATAN LOGAS TANAH DARAT KABUPATEN KUANTAN SINGINGI - Jumadianto '; Firdaus '; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The court's verdict is a statement issued by a judge to be pronounced in a public court hearing that aims to settle or terminate a civil case. The ruling is demanded for justice and what is important and decisive is the fact or event, the rule of law is a tool. As is the case in the upstream village of teso, kecamatan logas land, kuantan singingi district, where the implementation of the decision on the release of the land, it is considered an oddity, the process of execution of the verdict can not run properly, because the lack of clarity of law enforcers in decomposing Solving the root problem of land KKPA, in this study, the authors get the legal issues that should be raised in this thesis are: first how the implementation of the ruling of Pekanbaru high court against land disputes case Primary Members Cooperative Credit (KKPA) Hulu Teso Village Subdistrict Logas Tanah Darat Kuantan Singingi Regency ?, second Is the obstacle faced by bailiff of District Court in executing execution of KKPA KUD Langgeng Area Hulu Teso Village Subdistrict Logas Land of Kuantan Singingi Regency ?, third Is effort done by plaintiff to execute land decision Who is constrained in the settlement of his case ?.In this study the authors use the type of research that is juridical Normative, namely a study that discusses the principles of law, legal system, the level of legal synchronization, legal history, and comparison of law. Data collection techniques are Observation, Interview Methods, In this study the authors analyze the data qualitatively the data described descriptively from data that has been obtained.From the results of research and discussion the authors can conclude that the implementation of court decisions on execution of land KKPA tidan can be done by the plaintiffs, where the contents of the decision is still confused, it is dikeranakan by some constraints pendantanya does not contain where the litter location of the land in question, The efforts made by the plaintiffs are by conducting consensus negotiations against the defendants and local community leaders, but if this way also can not execute the plaintiffs will conduct a lawsuit again. Keywords: Implementation of Decision-Against KKPA Land